Does economic empowerment protect women against domestic violence? Evidence from the Philippines - S. Quimbo; X. Javier (University of the Philippines, School of Economics (UPSE), 2013)
Using data from the 2008 National Demographic and Health Survey, we ask whether women's economic empowerment -defined alternatively as having the ability to decide on (i) daily needs, (ii) major purchases, and (iii) spending own income - protects women against domestic violence. Using a simple model of choice of conflict resolution technology among spouses, we find evidence that economic empowerment protects women in a non-linear way. Low and high levels of empowerment reduce the likelihood of women experiencing domestic violence, possibly reflecting traditional gender roles in Philippine society.
Keywords: J12; J16; 330; Economic empowerment; domestic violence; Philippines